ECOLOGICAL DYNAMICS OF LOCAL PUBLIC ADMINISTRATION AGAINST GLOBAL TECHNOLOGICAL PRESSURES: GROK AI ON PLATFORM X - Indah Cahyani, Diva; Apriyani, Aini; Januariska, Dini; Dwilesty Nabila Indah Cahyani, Ardiva (LPPM, Universitas Muhammadiyah Riau, 2026)
The development of global artificial intelligence (AI) technology has had a significant impact on social and legal dynamics in Indonesia, one of which is through the use of Grok AI on the X platform (Twitter). This study aims to analyze the interaction between global AI technology and socio-political factors within the ecological framework of Indonesian public administration and examine the implications of the absence of specific AI regulations on the protection of people's digital dignity. The research method used is qualitative descriptive with a case study approach, through direct observation of user activities on platform X and documentation studies of regulations and related literature. The results of the study show that the absence of preventive AI regulations causes the abuse of Grok AI in the form of digital-based sexual harassment and visual manipulation without consent, thus causing ecological disturbances in the Indonesian public administration system. Government responses that tend to be reactive-adaptive, such as the temporary termination of access to Grok AI, reflect the limitations of the legal instruments available. This study concludes that it is necessary to update or establish AI regulations that are specific, binding, and preventive-oriented in order to protect the digital dignity of society and maintain the balance of the digital ecosystem in the midst of global technological pressures.